2000
DOI: 10.1097/00003226-200011000-00015
|View full text |Cite
|
Sign up to set email alerts
|

Six Different Mutations of TGFBI (βig-h3, Keratoepithelin) Gene Found in Japanese Corneal Dystrophies

Abstract: We conclude that codons R124 and R555 of the TGFBI gene are also hot spots in Japanese patients with ACD, LCD, GCD, and RBCD. Many Japanese patients with CD had ACD with R124H mutation. GCD with R555W mutation was rare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
5

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 23 publications
0
20
0
5
Order By: Relevance
“…No mutation was detected in 8 patients from four families with LCD or in the 50 normal volunteers. Table 2 shows the findings of our study including findings from Fujiki et al (2000), and findings of studies at two widely separated institutions in Japan (Mashima et al 2000). Codons R124 and R555 are hot spots in Japanese patients.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…No mutation was detected in 8 patients from four families with LCD or in the 50 normal volunteers. Table 2 shows the findings of our study including findings from Fujiki et al (2000), and findings of studies at two widely separated institutions in Japan (Mashima et al 2000). Codons R124 and R555 are hot spots in Japanese patients.…”
Section: Resultsmentioning
confidence: 93%
“…1. Interestingly, ACD with the R124H mutation is more common in Japanese patients than in Caucasians, and GCD with the R555W mutation, which is the classic form of GCD without lattice deposits, is rare in Japanese patients Fujiki et al 2000). Homozygous R124H or R555W mutation of this gene has been reported (Mashima et al 1997(Mashima et al , and 2000Fujiki et al 1998a;Okada et al 1998a and1998c).…”
Section: Resultsmentioning
confidence: 99%
“…Inherited mutations of the BIGH3 gene that have been associated with lattice corneal dystrophies were identified in several countries (8)(9)(10)(11). Among others, for CDL1, a Cto-T mutation at nucleotide position 417 in exon 4, leading to a R124C mutation within FAS1 domain 1, was frequently found in several families throughout the world (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported mutations in exons 11, 13, and 14 of the TGFBI gene in cases of lattice dystrophy. 1,7,15,16 As the proband of family 1 have not shown mutation in exons 4 and 12 we investigated exons 11, 13, and 14 but the sequence analysis have not detected mutation. Many reasons can explain this result.…”
Section: Discussionmentioning
confidence: 99%
“…2,4,5 Mutations in the TGFBI gene have been described in patients from many nationalities. [7][8][9][10][11][12] We report the first series of Brazilian patients screened for mutations in the TGFBI gene.…”
Section: Introductionmentioning
confidence: 99%